Coronin 1 trimerization is essential to protect pathogenic mycobacteria within macrophages from lysosomal delivery - Bosedasgupta S.; Pieters J. (My University, 2025)
Coronin 1 is a member of the evolutionarily conserved coronin protein family. Coronin proteins are characterized by the presence of a central WD repeat and a C-terminal coiled coil that in coronin 1 is responsible for trimerization. Coronin 1 was identified as a host protein protecting intracellularly residing mycobacteria from degradation by activating the Ca2+/calcineurin pathway but whether or not trimerization is essential for this function remains unknown. We here show that trimerization is essential to promote mycobacterial survival within macrophages and activate calcineurin. Furthermore, macrophage activation that induces serine-phosphorylation on coronin 1 resulted in coronin 1 monomerization. These results suggest that modulation of coronin 1 oligomerization is an effective way to determine the outcome of a mycobacterial infection in macrophages. © 2014 Federation of European Biochemical Societies. Published by Elsevier B.V. All rights reserved.